2020
DOI: 10.1002/car.2617
|View full text |Cite
|
Sign up to set email alerts
|

What Helps Children Tell? A Qualitative Meta‐Analysis of Child Sexual Abuse Disclosure

Abstract: The increasing use of qualitative methodologies to explore experiences of child sexual abuse (CSA) disclosure has led to the need to synthesise these findings. Recent reviews have tended to focus on the barriers to disclosure more than the facilitators or to conflate findings from studies of adults and studies of children and adolescents. This paper focuses on a qualitative meta‐analysis of studies conducted in the past 20 years (1998–2018) that addresses the question of what helps children disclose experience… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
58
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(66 citation statements)
references
References 34 publications
8
58
0
Order By: Relevance
“…As earlier studies (e.g. Thulin et al 2019; Reitsema & Grietens, 2016;Brennan & McElvaney, 2020;Jensen et al, 2005) have shown, disclosures of both CPA and CSA are often facilitated by addressing the topic at school or watching a TV program dealing with abuse. In addition, if the recipients of disclosure are peers (as they often are), they are probably faced with a moral dilemma of not disclosing confidential information and need guidance on how to report to a trusted adult (McGuire & London, 2020).…”
Section: Discussionmentioning
confidence: 96%
“…As earlier studies (e.g. Thulin et al 2019; Reitsema & Grietens, 2016;Brennan & McElvaney, 2020;Jensen et al, 2005) have shown, disclosures of both CPA and CSA are often facilitated by addressing the topic at school or watching a TV program dealing with abuse. In addition, if the recipients of disclosure are peers (as they often are), they are probably faced with a moral dilemma of not disclosing confidential information and need guidance on how to report to a trusted adult (McGuire & London, 2020).…”
Section: Discussionmentioning
confidence: 96%
“…Like Brennan and McElvaney's (2020) article on disclosure, the survey data in this paper suggest that contexts which value the views of young people cannot be created through guidance or process alone. Organisational cultures need to promote young people's participation and demonstrate this in their decision‐making processes: should this be achieved, Everley (2020, p. 126) argues that ‘the environment for children becomes more secure and practitioners benefit from the reflection that this provides them with’.…”
Section: Increasing Protection Through Contexts Of Listeningmentioning
confidence: 57%
“…Our first paper, by Emma Brennan and Rosaleen McElvaney (2020) from Dublin City University, Ireland, reports the results of a meta‐analysis of qualitative studies into CSA disclosure conducted from 1998 until 2018 to provide insights into what enables disclosure. Through a process of thematic analysis, six facilitators of disclosure emerge which the authors organise into two categories: dynamics that result in children ‘needing to tell’; and those where children have an ‘opportunity’ to tell.…”
Section: Contexts That Enable Disclosurementioning
confidence: 99%
See 2 more Smart Citations